Organização social sistematizada: controle social e regras de sociabilidade nos shopping centers. - Ribeiro, Paulo Henrique Montini dos Santos (2011)
Shopping centers have developed during the decades after the advent of capitalism and became a process of modernity. Shopping does have become institutions of modernity aimed to exert a socializing role of the consumer society. We indicate how to carry out various elements of social control of the institution and the means by which customers perceive and re-do these places through the lens of social facade built by its visitors, as any institution, the shopping center has models of social control who aim to frame his actors to their deviant role model. These control methods typify how we should act and what to do in these places, and thus create three types of customers: customers in common, ranging between normal clientele that fills the spaces of the shopping center, seeking anonymity, customers "caroço", considered a problem for sellers who treat them with some kind of social stigma, often ignored by sellers or simply badly treated, and repeat customers, customers that are able to circumvent many of these control rules through a knowledge gained through the practice of living together in the shopping. We chose these constructs models to try to understand a phenomenon very different from that observed by the vision of consumption itself, with the shopping center as a space that goes beyond the practice of consumption itself, turning into pure spaces of sociability, through its transformation private space in public, as a new interpretation of the border with the shopping street. This border is not as clearly defined among customers of the shopping center and the citizens of the city. The shopping center becomes an extension of the street.